INDONESIAN HALAL MSME OPEN INNOVATION WITH ISLAMIC FINTECH ADOPTION - Alfarizi, Muhammad; Ngatindriatun, Ngatindriatun (Jurnal Akuntansi dan Keuangan Indonesia, 2022)
The Fourth Industrial Revolution has led to the development of Islamic FinTech innovations to meet the needs of the Muslim community. This study analyzes the factors that determine the adoption of Sharia FinTech by halal MSME owners. The study utilized an exploratory method based on an online survey of halal MSME owners with 319 samples. The PLS-SEM analysis technique was chosen to prove the research hypothesis. This research finds that variables such as religiosity, Islamic financial literacy, and perception of risk affect the intention to adopt Islamic FinTech. The UTAUT2 variable has a positive effect on knowledge of Sharia FinTech adoption, while the adoption of Islamic FinTech positively impacts the sustainability of halal MSME businesses. The study recommends strengthening the infrastructure of the Sharia FinTech system and enhancing the value of financial services for halal MSMEs. Integrating Sharia FinTech into business operations can also enhance brand image and increase the sustainable business capacity of halal MSMEs. These insights can help develop effective strategies for Islamic FinTech innovation.